2021
DOI: 10.3390/polym13172930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminum Flakes on Mechanical and Optical Properties of Foam Injection Molded Parts

Abstract: Injection research using aluminum flakes has been conducted to realize metallic textures on the surface of plastic products. Several studies have focused on the effect of the orientation and quality of the flakes when using conventional injection molding methods; however, limited studies have focused on the foam injection molding method. In this study, we examined the orientation of aluminum flakes through foam injection with an inert gas and observed the changes in texture using a spectrophotometer and a glos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, the greatest inhibitory effect was observed against Escherichia coli with a zone of inhibition of 38.5 mm diameter followed by Bacillus subtilis with a zone of inhibition of 34.25 mm diameter at 6% w/w of ZnO-NPs concentration. Although ZnO-NPs usually have a stronger antimicrobial effect against Gram-positive bacteria such as Staphylococcus aureus [56] and Listeria monocytogenes [58,59], this study shows that these nanoparticles are also effective against Gram-negative bacteria. Previous studies have highlighted the use of ZnO nanostructures in different thermoplastic polymers to investigate antimicrobial and antifungal susceptibility [60].…”
Section: Antibacterial and Fungal Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the greatest inhibitory effect was observed against Escherichia coli with a zone of inhibition of 38.5 mm diameter followed by Bacillus subtilis with a zone of inhibition of 34.25 mm diameter at 6% w/w of ZnO-NPs concentration. Although ZnO-NPs usually have a stronger antimicrobial effect against Gram-positive bacteria such as Staphylococcus aureus [56] and Listeria monocytogenes [58,59], this study shows that these nanoparticles are also effective against Gram-negative bacteria. Previous studies have highlighted the use of ZnO nanostructures in different thermoplastic polymers to investigate antimicrobial and antifungal susceptibility [60].…”
Section: Antibacterial and Fungal Analysismentioning
confidence: 84%
“…The exact mechanism of ZnO-NPs inhibition is still a matter of debate among the research community, several authors have proposed: generation of reactive oxygen species (ROS), release of Zn 2+ ions and accumulation of nanoparticles in the cell membrane or cytoplasmic region [35]. In the release of Zn 2+ ions mechanism, the ions penetrate the cell wall of bacteria and eventually kill them; this liberation of active Zn 2+ rises with the concentration of ZnO-NPs in the resulting modified fiber, and thus enhances the inhibitory effect [56,57]. Furthermore, the greatest inhibitory effect was observed against Escherichia coli with a zone of inhibition of 38.5 mm diameter followed by Bacillus subtilis with a zone of inhibition of 34.25 mm diameter at 6% w/w of ZnO-NPs concentration.…”
Section: Antibacterial and Fungal Analysismentioning
confidence: 99%
“…Recently, Feng et al showed that the disturbance of the melt interface by the gas dissolved in the melt flow can lead to a tight interface at the weld line and mitigate the weld line 24 . Kim et al applied MIM to the fabrication of products containing aluminum‐added and studied the effect of aluminum flake content on mechanical properties 25 . However, the effect of MIM on the weld line of the products has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…24 Kim et al applied MIM to the fabrication of products containing aluminum-added and studied the effect of aluminum flake content on mechanical properties. 25 However, the effect of MIM on the weld line of the products has not been investigated. It is expected that the MIM process has potential advantages in the alleviation of weld lines and the improvement of mechanical properties in injection molded products containing aluminum pigments.…”
mentioning
confidence: 99%